Enterprise risk management in Europe - Maffei, Marco (Emerald Publishing Limited, 2021)
Enterprise Risk Management, governance systems and accounting practices are currently being applied to businesses without full coordination between them. The incorrect use of ERM models all over Europe could be hindering the potential benefits from its correct implementation and could constitute a barrier to the consolidation of a proper risk culture. Enterprise Risk Management in Europe advances understanding of ERM in Europe, providing a novel and unique set of perspectives on the ongoing dynamics between ERM and corporate processes. The contributors provide an in-depth analysis of the research benefits for the countries examined, looking at why, when and how ERM has developed over time. This book focuses on practical issues and identifying existing knowledge gaps, offering a fresh comprehension of the cultural and contextual factors surrounding its inception and further expansion. Also largely discussed is the role played by national and international regulatory and economic circumstances. Enterprise Risk Management in Europe is an essential guide for researchers, practitioners and policy makers both in and beyond European borders.